AKURASI KUALITAS DATA INFORMASI PADA SISTEM MANAJEMEN - Nurul Aini; Muhammad Irwan Padli Nasution (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
Data accuracy and information quality are crucial elements in effective decision- making within organizations. Data accuracy refers to the extent to which data reflects the intended values or events, while information quality encompasses various dimensions, including accuracy, accessibility, contextuality, and representational quality. The information audit process is used to assess and improve information quality within organizations by identifying needs, resources, and existing information flows. Additionally, issues related to information quality, such as excessive information volume, security, and lack of resources, can hinder organizational performance. Developing an effective data quality management (DQM) system, including the implementation of data catalogs and observability, is an important step in enhancing accuracy and information quality. With a systematic approach, organizations can achieve high data quality standards, which in turn will support better business decisions and improve customer satisfaction.